CD10 Expression in Non-Small Cell Lung Cancer - Glen Kristiansen; Karsten Schlüns; Yu Yongwei; Manfred Dietel; Iver Petersen (Analytical Cellular Pathology)
CD10 is a cell surface endopeptidase that inactivates various potentially growth stimulatory peptides. In lung cancer cell lines this downregulation has been associated with increased proliferation. Downregulation of CD10 in lung cancer tissue is described, suggesting a potential role in carcinogenesis and a possible use of CD10 as a prognostic marker. We aimed to determine the rate of CD10 expression in our non‐small cell lung cancer (NSCLC) collection and to clarify its correlation with clinicopathological parameters and patient survival. 114 NSCLC were analysed immunohistochemically using a monoclonal CD10 antibody (clone NCL‐CD10‐270) on an NSCLC tissue micro array. The staining was semiquantitatively scored. CD10 expression was observed in 19% of cases, without any significant association with tumour type, ‐size, ‐grading, nodal status, clinical stage, and patient survival time. We conclude that a diagnostic use of CD10 immunostaining in NSCLC is unlikely.